Strategi LPTQ Dalam Meningkatkan Kualitas SDM Yang Unggul dan ‎Qur’ani - Khairiyah Asri Nasution; Siti Suryani Hasibuan; Anggita Utami; Fakhrurrozi Hasibuan; Febri Ardiansyah; Ali Hardana (Indra Institute Research & Publication, 2022)
The existence of management as an art or science that regulates and manages an institution, agency, job or people in it is a means of achieving maximum goals through the implementation of management functions. However, sometimes problems arise due to a system that does not run well due to managerial weakness. So that it is necessary to implement comprehensive management to improve the quality and quality of human resources and other resources. Types of field research with a qualitative approach. Data mining is carried out with observation techniques, interviews, and documentation studies. Data analysis techniques are data collection, data reduction, data presentation and conclusion making. The results showed that the management implemented by LPTQ Padangsidimpuan City in an effort to improve the achievements of competition participants at the National Level Musabaqah includes (1) planning, namely meetings for the preparation of long-term and short-term programs and activities (2) organizing, namely efforts to determine the composition of the LPTQ Management, Provincial Level Judges Council and Trainers to prepare participants to face the National Level Musabaqah, (3) mobilization, namely efforts to organize Provincial-level MTQ/STQ to select outstanding participants and hold coaching and training for these outstanding participants in preparation for competing at the National level, (4) supervision, namely efforts to evaluate the achievements and results of the implementation of Musabaqah at the Provincial and National levels.